The Wife as the Primary Breadwinner of the Family: Perspectives from Classical Fiqh, Gender Studies, and Contemporary Fiqh - Hasanah, Uswatun; Irham, Muhammad Iqbal; Hamdani, Muhammad Faisal (Program Pascasarjana UIN Sumatera Utara, 2025)
In classical fiqh, the husband is regarded as the primary provider for the family. However, over time, the role has shifted, with wives increasingly contributing to the family's financial support—and in some cases, becoming the main breadwinner. This shift raises the question of how contemporary Islamic jurisprudence accommodates such changes without abandoning its foundational principles. This study aims to examine the role of the wife as the primary breadwinner from two perspectives: gender theory and contemporary fiqh. These perspectives offer a comprehensive understanding of women as main providers within the framework of Islamic law and gender studies. The study employs a qualitative method using a comparative analytical approach. The data sources include classical fiqh texts, academic literature on gender theory, and contemporary fiqh interpretations that recontextualize classical texts in light of modern social realities. A comparative analysis is conducted to explore the differences and intersections between gender perspectives and contemporary fiqh, thereby illustrating the conceptual dynamics and transformations. The findings reveal three distinct viewpoints. Classical fiqh confines the wife's role largely to the domestic sphere and household management, while assigning the primary financial responsibility to the husband. From a gender theory perspective, the wife's role as the main breadwinner is viewed as a manifestation of gender equality and the progress of women's emancipation. Meanwhile, contemporary Islamic scholars allow the wife to be the main provider, provided it is based on mutual consent and does not result in harm, although the fundamental obligation of financial support remains with the husband.